Broad_scale, dense amphipod tube aggregations on the sea bed: implications for resource species that utilize benthic habitats. (3rd November 2012) - VITALIANO, JOSEPH; PACKER, DAVID; REID, ROBERT; GUIDA, VINCENT
Abstract During a research cruise to Georges Bank in 1999 to study the areas closed to fishing, broad areas of the sea floor (3000_km2) were found to have a high percentage cover of emergent invertebrate tubes. Most of these tubes were attributable to the tubicolous epifaunal amphipod, Ericthonius rubricornis. Our data show the spatial extent that dense clumps of amphipod tubes could cover the sea floor on Georges Bank. When some of the same sites were sampled 1_yr later, in June 2000, the percent cover of the tube clumps on the sea floor was significantly reduced. Biogenic structures, such as invertebrate tubes, are important features of benthic habitats and may provide protection for juvenile fish and invertebrate resource species. Our observations reiterate that biogenic habitat characteristics are not spatially and temporally stable and this needs to be recognized by fisheries managers when managing the living marine resources that utilize these habitats.